2016
DOI: 10.1002/jsfa.8084
|View full text |Cite
|
Sign up to set email alerts
|

Using an enzymatic galactose assay to detect lactose glycation extents of two proteins caseinate and soybean protein isolate via the Maillard reaction

Abstract: This proposed enzymatic assay could directly detect lactose glycation of the two proteins, and thus was more useful than the four chemical indices to monitor glycation of the two proteins. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…Lactose-glycated caseinate was prepared via the Maillard reaction using the conditions as previously described (Wang & Zhao, 2017). In brief, the reaction system composed of caseinate (50 g/L) and lactose (80 g/L) at a pH value of 6.7, and was heated at a water bath (100°C) for 3 h with constant agitation.…”
Section: Preparation Of Two Glycated Caseinates and Tryptic Hydrolysatesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lactose-glycated caseinate was prepared via the Maillard reaction using the conditions as previously described (Wang & Zhao, 2017). In brief, the reaction system composed of caseinate (50 g/L) and lactose (80 g/L) at a pH value of 6.7, and was heated at a water bath (100°C) for 3 h with constant agitation.…”
Section: Preparation Of Two Glycated Caseinates and Tryptic Hydrolysatesmentioning
confidence: 99%
“…GC-I hydrolysate was hydrolyzed by 2 mol/L trifluoroacetic acid at 100°C for 4 h as previously described (Račaitytė, Kiessig, & Kálmán, 2005), cooled to ambient temperature, neutralized into pH 7.0 using 2 mol/L NaOH, and then detected for galactose content as per the study (Wang & Zhao, 2017) using the galactose assay kit and procedure provided by the kit producer. Lactose content (g/kg protein) was thereby calculated chemically.…”
Section: Chemical Analysesmentioning
confidence: 99%
“…To assay lactose content of the glycated digest, the sample was hydrolyzed by 2 mol/L trifluoroacetic acid at 100 °C for 4 h, cooled to 20 °C, and neutralized with 0.5 mol/L NaOH solution. The obtained hydrolysate was detected for galactose content and then calculated for lactose content (g/kg protein), as previously described [ 19 ].…”
Section: Methodsmentioning
confidence: 99%
“…Compared with the unglycated digests, whether the glycated digests have increased or decreased bioactivity to the body is absolutely important. Two previous studies by our group had found that the lactose-glycated caseinate digest had poor ability compared with the unglycated caseinate digest to promote barrier integrity of rat intestinal epithelial (IEC-6) cells or to combat against the camptothecin-induced apoptosis in IEC-6 cells [ 19 , 20 ]. Whether the lactose-glycated digest has a changed in vivo activity toward the weaned animals than the unglycated digest, for example, the vital body growth and intestinal development, is not investigated yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation